Stimulation in the Rat Anterior Insula and Anterior Cingulate During an Effortful Weightlifting Task - Silva, Carlos; Porter, Blake S.; Hillman, Kristin L. (Frontiers in Neuroscience, 2021)
When performing tasks, animals must continually assess how much effort is being expended, and gauge this against ever-changing physiological states. As effort costs mount, persisting in the task may be unwise. The anterior cingulate cortex (ACC) and the anterior insular cortex are implicated in this process of cost-benefit decision-making, yet their precise contributions towards driving effortful persistence are not well understood. Here we investigated whether electrical stimulation of the ACC or insular cortex would alter effortful persistence in a novel weight-lifting task (WLT). In the WLT an animal is challenged to pull a rope 30 cm to trigger food reward dispensing. To make the action increasingly effortful, 45 g of weight is progressively added to the rope after every 10 successful pulls. The animal can quit the task at any point – with the rope weight at the time of quitting taken as the ‘break weight.’ Ten male Sprague-Dawley rats were implanted with stimulating electrodes in either the ACC (cingulate cortex area 1 (Cg1) in rodent) or anterior insula and then assessed in the WLT during stimulation. Low-frequency (10 Hz), high-frequency (130 Hz) and sham stimulations were performed. We predicted that low-frequency stimulation of Cg1 in particular would increase persistence in the WLT. Contrary to our predictions, low-frequency stimulation of Cg1 resulted in shorter session duration, lower break weights, and fewer attempts on the break weight. High-frequency stimulation of Cg1 led to an increase in time spent off-task. Low-frequency stimulation of the anterior insula was associated with a marginal increase in attempts on the break weight. Taken together our data suggest that stimulation of the rodent Cg1 during an effortful task alters certain aspects of effortful behavior, while insula stimulation has little effect.